Declining Marine Survival of Steelhead Trout Linked to Climate and Ecosystem Change - Jan Ohlberger; Eric R. Buhle; Thomas W. Buehrens; Neala W. Kendall; Toby Harbison; Andrew M. Claiborne; James P. Losee; Jennifer Whitney; Mark D. Scheuerell (Fish and Fisheries, 2025)
Species with complex life cycles, such as anadromous fish that perform spawning migrations between freshwater and the ocean, may be particularly sensitive to global change because freshwater and marine habitats experience distinct shifts in climate and ecosystem dynamics. Abundances of wild steelhead trout ( Oncorhynchus mykiss ) have declined across most of their range over the past 40–50 years. We examined whether declines in steelhead survival can be linked to changing climate conditions and species interactions. A novel hierarchical integrated population model that accounts for the species' complex life history was fitted to data from multiple wild steelhead populations on the Washington coast, U.S.A. The model estimates recruitment residuals and kelt survival rates as time‐varying processes, which reflect annual variation in survival before and after first maturation. We found that survival rates of immature steelhead (recruits) and adult steelhead (kelts) have declined over time and that survival trends across populations were strongly associated with climate and ecosystem change, specifically summer sea surface temperature and pink salmon abundance in the North Pacific Ocean, the NPGO index and river flows. Including these drivers in the model reduced unexplained annual variation in shared recruitment and kelt survival anomalies and largely accounted for their negative long‐term trends. Our findings provide evidence that rising temperatures and increased interspecific competition at sea have contributed to declines in steelhead survival over the last five decades. Considering projected warming and high pink salmon abundances in the ocean, steelhead will likely continue to experience low marine survival rates.

Bait Biomass and Caloric Contribution From the Dungeness Crab ( Cancer magister ) Fishery in Oregon, USA - Toby Harbison; Sarah K. Henkel (Fisheries Management and Ecology, 2025)
Fishery discards worldwide increase the availability of organic materials on the benthos, altering trophic relationships and potentially increasing the abundance of benthic consumers. Expert knowledge from fishers is a valuable yet often underutilized source of information to understand these dynamics. We interviewed Dungeness crab fishers ( n = 24) to determine the most‐used bait types and to characterize regional and seasonal bait use strategies that drive inputs of organic matter into Oregon coastal waters during the commercial Dungeness crab fishery each year. Based on bomb calorimetry measurements of caloric densities of 12 commonly reported bait species, total energetic input was 12.99 × 10 9 kJ (3.10 B kcal) from bait in the 2019–2020 commercial ocean Dungeness season in Oregon, USA. Fishing effort and bait inputs were strongly seasonal, with 88% of effort concentrated in the first 60 days of the 9‐month‐long season but did not vary regionally. This large, temporally concentrated caloric input suggested that bait could contribute substantially to Dungeness crab productivity. Fisher respondents indicated that bait effectiveness was the most important motivating factor in choosing a bait type, more than availability or cost.